Prinsip Kerja Sama Tuturan Deklaratif Narasumber dalam Kanal Youtube Najwa Shihab Episode “Terima Kasih Pak JK” - Mila Widayanti; Herwandi Herwandi (UIR Press, 2023)
This study aims to determine the purpose of using declarative utterances and to find out the sources of declarative utterances that meet the principle of cooperation in the use of declarative utterances on Najwa Shihab's youtube channel episode